Pengaruh Ekstrakurikuler Pramuka Terhadap Kemandirian Siswa Kelas V SDN Cibodas Kota Tangerang - Desi Ramadanti; Sunardin Sunardin; Rahmawati Eka Saputri (Journal on Education, 2023)
This study evaluates the influence of Scout extracurricular activities on self-directed learning in 5th-grade students at SDN Cibodas, Tangerang City. Data collected includes pre and post assessments of students' self-directed learning. The study involved 57 students divided into control and experimental groups. Results indicate a significant difference in self-directed learning between the two groups. Students who participated in Scout activities showed a notable improvement in self-directed learning compared to non-participating students. These findings support the hypothesis that Scout extracurricular activities positively impact students' self-directed learning. The implications highlight the importance of Scouts in fostering student independence. Through Scout activities, students develop crucial skills such as self-directed learning and problem-solving. This insight guides schools and stakeholders in designing holistic educational programs that prioritize the integration of Scout extracurricular activities. Additionally, this research contributes to the existing literature on the influence of extracurricular activities on student development. The findings serve as a foundation for further research investigating additional factors influencing the impact of Scout activities on students' self-directed learning. It also informs the development of more effective extracurricular programs aimed at enhancing students' self-directed learning abilities